Faktor yang Berhubungan dengan Kejadian Filariasis di Desa Denduka Kecamatan Wewewa Selatan Kabupaten Sumba Barat Daya - Melkianus Bulu; Pius Weraman (Media Kesehatan Masyarakat, 2021)
Filariasis is a chronic infectious disease caused by filarial worms and transmitted by mosquitoes. In 2017, a total of 113 filariasis cases were reported in Southwest Sumba Regency of which 35 cases were found in Puskesmas Tena Teke. Denduka village recorded 18 cases. This study aims to analyze factors related to the incidence of filariasis in Denduka Village. This research was analytical observational with cross-sectional design. The sample consisted of 100 people. The data were analyzed using chi square (α=0.05). The results showed that the presence of mosquito breeding places (p-value= 0.020) and shrubs (p-value= 0.020) related to the incidence of filariasis while age (p=0.799), gender (p-value=1,000), occupation (p-value=0.554), income (p-value=1,000), net use (p-value=0.065) and duration of work (p-value=0.055) were unrelated to the incidence. The community needs to reduce contact with vectors by frequently cleaning houses and surrounding environment, and using mosquito nets while sleeping.